2005
DOI: 10.1084/jem.20050203
|View full text |Cite
|
Sign up to set email alerts
|

In situ characterization of CD4+ T cell behavior in mucosal and systemic lymphoid tissues during the induction of oral priming and tolerance

Abstract: The behavior of antigen-specific CD4+ T lymphocytes during initial exposure to antigen probably influences their decision to become primed or tolerized, but this has not been examined directly in vivo. We have therefore tracked such cells in real time, in situ during the induction of oral priming versus oral tolerance. There were marked contrasts with respect to rate and type of movement and clustering between naive T cells and those exposed to antigen in immunogenic or tolerogenic forms. However, the major di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
138
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(148 citation statements)
references
References 32 publications
(113 reference statements)
10
138
0
Order By: Relevance
“…Time points between stacks ranged from 18 to 48 s depending on the settings for each experiment. Multi-dimensional rendering was performed with Imaris (Bitplane) and cell tracking was performed with PicViewer Software (John Dempster University of Strathclyde) [16].…”
Section: Methodsmentioning
confidence: 99%
“…Time points between stacks ranged from 18 to 48 s depending on the settings for each experiment. Multi-dimensional rendering was performed with Imaris (Bitplane) and cell tracking was performed with PicViewer Software (John Dempster University of Strathclyde) [16].…”
Section: Methodsmentioning
confidence: 99%
“…However, in a growing fraction of the industrialized world, contact, ingestion, or inhalation of such allergens provokes harmful and sometimes fatal allergic responses (1,2). It appears that the nature of the Ag, the specific tissue microenvironment at the site of initial encounter, and molecular events in the draining lymph node (LN) 3 are critical in establishing whether long-lived immunity or tolerance prevails (3)(4)(5)(6)(7)(8).…”
Section: Inhalation Tolerance Is Induced Selectively In Thoracic Lymphmentioning
confidence: 99%
“…The decision for a T cell to ''stop'' and form long-lived contacts with a DC when scanning for cognate antigen may depend on multiple parameters, but antigen density (12) and peptide affinity for class II (19) have been shown to augment the frequency of prolonged DC:T cell contacts, increasing the efficiency of the T cell stop signal. Recent studies have also suggested the requirement of stable DC:T cell interactions for the induction of immunity, rather than tolerance (15,(20)(21)(22). Strikingly, recent publications suggest that peptide:class II complexes that persist for long periods of time may be an essential feature of a germinal center reaction (23,24).…”
mentioning
confidence: 99%
“…However, it is unknown whether these low-stability peptide:class II complexes are otherwise competent to recruit CD4 T cells if intracellular antigen processing is bypassed. The need for extended interactions of antigen-bearing APC by CD4 T cells (15,(20)(21)(22) suggests that persistence of cell surface complexes may be a generalized feature of the ability of a peptide to recruit T cells. To explore this issue, we evaluated whether CD4 T cell responses to low-stability peptide:class II complexes can be sustained over time.…”
mentioning
confidence: 99%
See 1 more Smart Citation